KOMPONEN FAKTOR ABIOTIK LINGKUNGAN TEMPAT TUMBUH PUSPA (Schima wallichii DC. Korth) DI KAWASAN HUTAN ADAT BULIAN KABUPATEN MUSIRAWAS : Components Of Environmental Abiotic Factors Where Grow Puspa (Schima wallichii Dc. Korth) In Bulian Traditional Forest Area Musirawas District - Nursanti Nursanti; Ade Adriadi Adriadi; Sai'in Sai'in (Jurnal Silva Tropika, 2021)
The puspa plant (Schima wallichii) is a tree species that is widely used as building raw material, producing firewood, making paper, furniture industry, animal feed, traditional herbal medicine and producing dyes. Puspa Plants in the Bulian Customary Forest Area Grows in environmental conditions with a flat topography, namely at a slope of 0%-5%, alluvial soil type, pH conditions ranging from 5-6 and brown soil color, clay texture, dusty clay, to dusty clay loam with a percentage of 2%-9% sand per ticket, 21%-64% dust particles and clay particles ranging from 33%-75%. The nutrient content of N ranges from 0.15% - 0.2%; nutrient K ranges from 0.01% - 0.02%; nutrient Ca ranges from 0% - 0.06%; Mg nutrients ranged from 0.01% - 0.04% and P nutrient content from 4.64 me/100g to 17.27 me/100g. While the abiotic component of climatic factors, puspa plants grow in environmental conditions with daily light intensity ranging from 112.25 lux - 2156.25 lux, temperature and humidity ranging from 28.30C - 30.60C while daily humidity ranges from 85.25% - 96.25%.Keywords: Abiotic Factors, Puspa Plant (Schima wallichii), Bulian Traditional Forest